On the Discrete-Time GeoX/G/1 Queues under N-Policy with Single and Multiple Vacations - Sung J. Kim; Nam K. Kim; Hyun-Min Park; Kyung Chul Chae; Dae-Eun Lim (Journal of Applied Mathematics)
We consider the discrete-time GeoX/G/1 queue under N-policy with single and multiple vacations. In this queueing system, the server takes multiple vacations and a single vacation whenever the system becomes empty and begins to serve customers only if the queue length is at least a predetermined threshold value N. Using the well-known property of stochastic decomposition, we derive the stationary queue-length distributions for both vacation models in a simple and unified manner. In addition, we derive their busy as well as idle-period distributions. Some classical vacation models are considered as special cases.